HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU HAMIL TENTANG DAMPAK PENYAKIT MALARIA PADA KEHAMILAN DI KLINIK ADRIANA TARIGAN BELAWAN - Erlina Hayati; Suriani Suriani (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2018)
Malaria is still a major health problem in 107 countries in the world. This disease attacks at least 350-500 million people every year and causes the death of about 1 million people every year or one baby or child dies every 30 seconds. It is estimated that around 3.2 billion people live in malaria endemic areas. Malaria also has an economic effect on losing 12% of national income, countries that have malaria. The total malaria sufferers in the world reaches 3.3 million people per year, the most (80 percent) in Africa and 20 percent in Asia. Malaria is a disease that is still a problem in the world. Malaria is an infectious disease that can be acute or chronic, caused by Protozoan Genus Plasmodium characterized by fever, anemia and splenomegaly. Malaria infection in pregnancy is very detrimental to the mother and fetus it contains, because this infection can increase the incidence of maternal and fetal morbiditis and mortality. This study is an analytic study, a cross sectional survey that is to connect knowledge with the attitude of pregnant women about the impact of malaria at the Clinic of Adriana Tarigan Belawan in 2014, technical sampling by total sampling, taking all populations into a sample of 30 people. The type of data used is primary data, which is obtained from filling out a questionnaire filled in by pregnant women, including the knowledge and attitudes of pregnant women about the impact of malaria treatment in pregnancy. The results of this study indicate that the majority of good knowledge respondents were 18 people (60.0%), a positive attitude of 15 people (50.0%). After statistical tests with quadratic test obtained df = 2 and p-Value = 0.028 <0.05 by because (P) <0.05, the conclusion is that Ha is accepted means that there is a signification relationship between the knowledge of pregnant women about the impact of the disease malaria in pregnancy. From the results of this study it can be concluded that knowledge has a significant relationship with attitudes based on the characteristics of age, education, work of pregnant women. It is expected for pregnant women to increase their knowledge especially about the impact of malaria during their pregnancy.